Literature Review/Qualitative Literaturanalyse. "Gestaltung von Mensch-Maschine-Schnittstellen: Zur Usability digitaler Lesemedien" - Sibylle Kunz (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2018)
– Digital reading media can be described as a mixture or blend of information and software and thus represent a new kind of media, coming in many forms and possibilities of reception. Therefore many scientific disciplines get engaged in "digital reading", the changes in the ways of reception, the implications for media producers, consumers and prosumers. This literature review presents a general overview of the most relevant contributions in the fields of reading and media research, linguistics, cognitive neuroscience, media design, media economics and computer science as well as information systems. It presents a first approach of the desideratum "digital reading media" based on available contributions. One finds that especially in the field of computer science there are still deficits concerning a structured model-based approach. Up to now there's a lack of strictly analytical, structured and usability-focused models of these media as for their properties, functionalities and design of the human-computer interface. Instead we find that the debate is very often emotionally motivated and electronic media are mostly described transferring terms and properties of the analogue print books, newspapers or journals, neglecting uniquely digital properties.
urn:nbn:de:bvb:29-opus4-99101
Keywords: 650; Digitale Lesemedien; E-Book; Usability; Oberflächengestaltung; Mensch-Maschine-Interaktion; Informationsarchitektur